Effect of Medium on the Activity of Eugenol: A Mini-Review - Rege, Sameera A.; Varshneya, Megha A.; Momin, Shamim A. (Current Nutrition & Food Science, 2022)
The role of essential fatty acids is vital in the life of a human being. The lack of essential fatty acids causes various diseases, such as cardiovascular, inflammatory bowel, and obesity. Although synthetic antioxidants have already been used, nowadays, the demand for natural antioxidants has increased mainly because of the adverse effects of synthetic antioxidants. Spices are widely used in this context as a source of natural antioxidants. It has been observed that they also act as pro-oxidants. This review aims to evaluate the fundamental reason for the different activities of the spices by studying the example of eugenol, a principal phenolic constituent of clove oil. The chemistry concerning the mechanism to display antioxidant and pro-oxidant activity is currently being reviewed. The isomerization of eugenol to isoeugenol plays a key role in exhibiting dissimilar behaviour of the eugenol. Under the polar medium, isomerization of eugenol does not take place, and it acts as an antioxidant. However, in the non-polar medium, eugenol isomerizes to isoeugenol and displays a pro-oxidant effect. In the basic medium, eugenol isomerizing to isoeugenol undergoes degradation. Hence, to utilize the beneficial activity of eugenol, it should be present in a polar or acidic medium. It can be concluded from this review article that the structural form of any molecule plays a major role in utilizing its activity and is also dependent on the medium. Hence, the medium also performs a vital role in influencing the activity of any molecule.
Keywords: Essential fatty acids